Micro- and Macroeconomic Models and Optimization Procedures - Sándor Karajz (Theory, Methodology, Practice, 2013)
The conventional economics lies on the fundamental assumption of neoclassical welfare economics according to which the primarily aim of economics is to achieve Pareto optimal conditions. Pareto optimum has two meanings: if Pareto optimum means Pareto norms, it reflects relevant conditions for economic policy. If Pareto optimum is linked with marginal analysis when a determined fictitious economic optimum is sought for in a perfect competition situation, it an instrument used for formal analytical analysis. According to this allocation of resources or the volume of production is optimal if there is a situation in which it is possible to make any individual better off without making someone else worse off.